Analysis of the Synergistic Effect of Antibiotics with Copper Oxide Nanoparticles Against Pseudomonas aeruginosa Isolated from Different Clinical Cases - Rusl Ahmed Mahdi Saleh; Harith Ahmed Mustafa (Tikrit Journal of Pure Science)
Synergism between antibiotics and nanoparticles is one of the most important ways to combat antibiotic resistance. Copper nanoparticles were produced using a green, environmentally friendly method of mixing  aqueous Ficus Sycomorus leaf extract with copper sulfate. The work aimed to study the synergistic effect of six antibiotics with copper oxide nanoparticles prepared in a green approach against bacteria Pseudomonas aeruginosa isolated from patient. A total of 110 specimens were collected from patients with burn, wound and urine infections. in Samarra General Hospital, Tikrit Teaching Hospital, Tikrit Military Hospital, and Baghdad Medical City of both genders from July to September 2023. A bacteriological examination was conducted to select bacterial pathogens, with a particular focus on Pseudomonas aeruginosa. From a total 110 cases, 50 (45.5%) gave positive cultures for Pseudomonas aeruginosa. CuO-NPs was characterized using different analytical techniques, Scanning Electron Microscope (SEM). showed that the CuO-NPs have a spherical shape, its average size is 29.2 nm. Energy-dispersive X-ray )EDX( results confirmed the presence of copper and oxygen in the composition. The synergistic effect of six antibiotics with CuO-NPs was studied. By evaluating the minimum inhibitory concentration of P. aeruginosa. The results show the highest inhibition against bacterial isolates was due to the synergistic effect of CuO-NPs with Impenem, Ciprofloxacin, Ceftazidime, Polymyxin B, Amikacin, and Cefepime respectively, especially on isolate (15) with zones of inhibition/mm were 19.33 ±0.33, 18.33 ±0.33,  16.33 ±0.33, 15.33 ±0.33, 14.67 ±0.33, and 12.7±0.58, respectively. The results indicated that the synergistic effect gave clear zones of inhibition against all isolates compared with the inhibition effect of nano-copper oxide and antibiotics.